Active surveillance for clinically localized prostate cancer––A systematic review. Issue 8 (7th March 2014) - Thomsen, Frederik B.; Brasso, Klaus; Klotz, Laurence H.; Røder, M. Andreas; Berg, Kasper D.; Iversen, Peter
<x xml:space="preserve">Abstract</x> Active surveillance (AS) has been introduced as an observational strategy to delay or avoid curative treatment without compromising long‐term cancer‐specific survival. The 10 studies included in this review, published between 2008 and 2013, generally agreed upon patients selection for the AS strategy and how they should be managed within the program. However, uncertainties persists concerning optimal patient selection and reliable progression criteria, as well as the long‐term safety of AS. J. Surg. Oncol. 2014 109:830–835. © 2014 Wiley Periodicals, Inc.